ANALYSIS OF MOTOR DEVELOPMENT PROJECT PARTICIPANTS COPAME (Fiep Bulletin - online, 2013)
The aim of the study was to identify the motor ages of children participants COPAME Project. The motor profile of each individual practitioner was drawn according to Motor Development Scale described in the Evaluation Manual motor, the kind of research was qualitative description. The sample consisted of 26 students, of both sexes, aged between 3 and 12 years, participants in Project COPAME - extension project at the University of Santa Cruz do Sul (UNISC). Testing was done with the aid of EDM Kit (Motor Development Scale). For data analysis we used the EPI-INFO version 6.0 (Fernández Merino, 1996). Tests were performed to assess Global Kinetics, Body Scheme and Temporal Organization. The results show that most children in the sample had Motor Age less than its chronological age. In the area of ??global motor, the entire sample was found within the normal range. In terms of body schema, the sample were classified as Low and Very Low. In a general analysis of the aspects evaluated did not show satisfactory results, however this is indicative that must be addressed solutions for improving motor performance of these practitioners, taking into account social vulnerability because they are housed in an institution for minors, and his period in this environment is unstable, noting that the results of individuals who are no longer in the project were the best. Thus, according to the study results, one can draw an individualized treatment to improve motor performance of these practitioners. Therefore believed to be of paramount importance a program of assessment, monitoring and intervention of motor development, with a view to promoting children's health and the prevention of infectious diseases development.
Keywords: Motor Development; Children; Vulnerability